Implementasi SAK ETAP Pada Laporan Keuangan Koperasi Konsumen Politeknik Elpetigai Tasikmalaya - Yuliani, Elfin (POLITEKNIK LP3I, 2024)
This study aims to analyze the suitability of the Financial Statements Implementation of the Consumer Cooperatives of the Tasikmalaya Polytechnic Elpetigai (KOPELTAS) with SAK ETAP (2016 Edition). Data were collected using documentation and interviews. After the data is collected, a descriptive analysis is carried out starting with a comparison between the sample financial statements and SAK ETAP (2016 Edition). Based on the results of the analysis, it shows that the Consumer Cooperative of Tasikmalaya Elpetigai Polytechnic (KOPELTAS) is not accordance with SAK ETAP, because it does not present a tax expense account on the income statement, there is a double record in the retained earnings reserve account which should be closed every year, then it is proven that it does not prepare a Cash Flows Statement that should be made each reporting period.